Deriváty kyseliny fenylkarbamové jako potenciální antituberkulotika - Waisser, Karel; Cizmárik, Jozef (Ceska a Slovenska farmacie, 2012)
Basic esters of phenylcarbamic acid were studied by the teams of Prof. Cizmárik and Prof. Waisser as potential antituberculotics. Their antimycobacterial activity increased with lipophilicity. The most active derivatives were substituted with an alkoxy group in position p- on the phenyl. The activity of some of them almost approached that of INH, but they exceeded it only in the evaluation against the INH-resistant strains M. avium and M. kansasii. The carbamates produced by Prof. Vinsová and co-workers published in the last year show that carbamates can be still topical.
Keywords: karbamáty; antituberkulotika; Mycobacterium; Antitubercular Agents; Carbamates